EFEKTIVITAS PELAKSANAAN PROGRAM PENGEMBANGAN USAHA EKONOMI PEREMPUAN PADA BADAN PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK, KEPENDUDUKAN DAN KELUARGA BERENCANA PROVINSI SULAWESI TENGGARA - Takwim Takwim (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This study aims to find out and analyze: The Effectiveness of the Implementation of Women's Economic Development Program at Women's Empowerment, Child Protection, Population and Family Planning in Southeast Sulawesi Province The method used is qualitative research with descriptive analysis. The data obtained comes from interviews, observations and document studies. The results showed that the Effectiveness of the Implementation of Women's Economic Development Program, the Women's Empowerment Agency, Child Protection, Population and Family Planning in Southeast Sulawesi Province has been implemented in accordance with established procedures, but not yet optimal. Keywords: Effectiveness of the Implementation of Women's Economic Developmen, Program at the Agency for Women's Empowerment, Child Protection, Population and Family Planning in Southeast Sulawesi Province